2017
DOI: 10.18203/2394-6040.ijcmph20173711
|View full text |Cite
|
Sign up to set email alerts
|

Injury and violence related behaviour among school-going adolescents in Jammu region

Abstract: INTRODUCTIONMany adolescents face physical, psychological and social challenges of various kinds. They usually start experimenting with risky health behaviours on certain occasions before intensifying and consolidating it.1 These high-risk behaviours include those which contribute to unintentional injuries, violence, alcohol and other drug use, and tobacco use, sexual behaviours related to unintended pregnancy and sexually transmitted infections, Unhealthy dietary behaviours and inadequate physical activity. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
0
1
Order By: Relevance
“…Further, the current study found that the prevalence of not wearing a helmet amongst those who rode a two-wheeler vehicle in the past 30 days was 42.6%. This finding is similar to the 40% and 46% reported by Kumar et al [11] (Jammu, 2017) and Abayomi et al [18] (Nigeria, 2015). The current study also depicts that the odds of indulging in road risk behavior were higher among students who drank alcohol, abused substances, and belonged to a rural area than their counterparts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further, the current study found that the prevalence of not wearing a helmet amongst those who rode a two-wheeler vehicle in the past 30 days was 42.6%. This finding is similar to the 40% and 46% reported by Kumar et al [11] (Jammu, 2017) and Abayomi et al [18] (Nigeria, 2015). The current study also depicts that the odds of indulging in road risk behavior were higher among students who drank alcohol, abused substances, and belonged to a rural area than their counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Peltzer and Pengpid (2015) [15], in their study conducted amongst University students across 26 countries, also reported the prevalence of drinking and driving as 17.3%. However, the prevalence rates in the current study were higher than those observed by Kumar et al [11] (Jammu, 2017); Nagalingam et al [16] (Chennai, Tamil Nadu; 2016); Cacodcar and Naik [17] (Goa, 2015); as they reported riding with an intoxicated driver to be 14.7%, 12.5%, and 10.7% respectively. This difference can be due to the different study settings; almost half the participants in these studies belonged to rural areas compared to 25% in the present study.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation